Discordant renal progression of Fabry disease in male monozygotic twins: a case report - Lee, Do-Yun; Jeong, Jun-Yeong; Lee, Seung-Eun; Lee, Jae-Hun; Moon, Ju-Young; Jung, Su Woong; Lee, Sang-Ho; Kim, Yang Gyun (Frontiers in Genetics, 2023)
Background: Fabry disease (FD) is a rare X-linked lysosomal storage disease caused by mutations in the GLA gene that encodes α-galactosidase A (α-GAL). Clinical phenotypes tend to vary in monozygotic female twins because mutations are located on the X-chromosome, whereas similar phenotypes are found in male monozygotic twins. Here we report the case of male monozygotic twins with FD presenting with distinguishable renal phenotypes. Case: A 49-year-old male patient who visited the hospital with proteinuria 14 years prior was readmitted for the same issue. His monozygotic twin brother had started hemodialysis 6 months prior due to renal failure of unknown origin. The patient’s renal function was within the normal range, while his spot urine protein-to-creatinine ratio was 557 mg/g. Echocardiography revealed left ventricular hypertrophy (LVH). The findings of a renal biopsy were consistent with FD. Genetic testing identified a c.656T>C mutation in the GLA gene, and α-GAL activity was significantly decreased. Genetic screening of his family clarified that his mother, older sister, twin brother, and his daughter had the same genetic mutations. The patient received enzyme replacement therapy 34 times. Subsequently, migalastat was initiated that continues today. Renal function and proteinuria remain stable, and the LVH has mildly improved. Conclusion: This is the first case of male monozygotic twins expressing different progressions of FD. Our findings demonstrate the possibility that environmental or epigenetic factors may critically influence genotype–phenotype discordance.